BACE1 RNAi Restores the Composition of Phosphatidylethanolamine-Derivates Related to Memory Improvement in Aged 3xTg-AD Mice - Villamil-Ortiz, Javier G.; Barrera-Ocampo, Alvaro; Piedrahita, Diego; Velásquez-Rodríguez, Claudia M.; Arias-Londoño, Julian D.; Cardona-Gómez, Gloria P. (Frontiers in Cellular Neuroscience, 2016)
β-amyloid (Aβ) is produced by the β-secretase 1 (BACE1)-mediated enzymatic cleavage of the amyloid precursor protein through the amyloidogenic pathway, making BACE1 a therapeutic target against Alzheimer’s Disease (AD). Alterations in lipid metabolism are a risk factor for AD by an unknown mechanism. The objective of this study was to determine the effect of RNA interference against BACE1 (shBACEmiR) on the phospholipid profile in hippocampal CA1 area in aged 3xTg-AD mice after 6 and 12 months of treatment compared to aged PS1KI mice. The shBACEmiR treatment induced cognitive function recovery and restored mainly the fatty acid composition of lysophosphatidylethanolamine (LPE) and etherphosphatidylethanolamine (ePE), reduced the cPLA2’s phosphorylation, down-regulated the levels of arachidonic acid (AA) and COX2 in the hippocampi of 3xTg-AD mice. Together, our findings suggest, for the first time, that BACE1 silencing restores phospholipids composition which could favor the recovery of cellular homeostasis and cognitive function in the hippocampus of triple transgenic AD mice.